Analisis Kesesuaian Kompetensi Dasar dengan Bahan Ajar Bahasa Arab MTs Kelas IX Karya Yushi M. Mahmudah - Ali Mufti; Mudrofin Mudrofin (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2021)
The Indonesian Ministry of Religion has published Arabic textbooks for ninth grade to assist the implementation of the revision of the Core and Basic Competencies. The purpose of this research is to evaluate the compatibility of Arabic teaching materials with the Basic Competencies outlined in KMA No. 183 of 2019. The study employs a library research design with the data collected using documentation. The sample was selected using purposive sampling techniques, namely the content examination and assessment. Content analysis was performed to analyze the data. The results showed that some contents of the textbook did not comply with the requirements of the basic competence. Several readings and conversational texts did not instance of grammatical structures in use. The textbook did not contain practice questions for mahrah istima'. Also, only 13 (out of 34) questions in the mahārah istimā' segment pertain to higher-order thinking skills (HOTS), while the majority of the questions in mahārah kalām and kitābah pertains to the basic competence of 2013 Curriculum.